Formation of students' adaptive abilities at sambo classes - A V Martyshov (RUDN Journal of Ecology and Life Safety, 2011)
The article discusses the opportunities of improving the quality of the learning process of school students through developing their adaptability to stress factors, which results in a better physical condition, improved academic and physical performance of students.